Average gonadotropin dosage per follicle as a predictor of ovarian response - Mudiyarasan, Shanthini; Shankar, Kundavi; Veerasigamani, Geetha; Rashmi; Ranji, Geovin; Asokan, Yamini; Radhakrishnan, Hemaniveda Kancheepuram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: In ovarian stimulation, oocytes retrieved are commonly used to assess response to gonadotropins. Markers like FORT, FOI, and OSI have been proposed but show poor prediction of IVF outcomes. Each is limited by various clinical and technical factors. A novel index, average gonadotropin dosage per preovulatory follicle offers better prediction of ovarian response and clinical pregnancy rate, aiding in personalized stimulation and helping anticipate OHSS risk and cycle cancellations Methods: This retrospective cohort study included 238 sub fertile women who underwent IVF at the Institute of Reproductive Medicine, Madras Medical Mission Hospital, from January 2019 to December 2023. It aimed to evaluate a new marker, average gonadotropin dosage per preovulatory follicle as a predictor of ovarian response and pregnancy outcomes. The index was calculated by dividing the total gonadotropin dose by the number of 16–22 mm follicles on trigger day. Patients were grouped by the 50th percentile, and stimulation parameters, MII oocyte ratio, clinical pregnancy rate, and live birth rate were compared between groups. Results: Group A showed significantly higher oocyte yield, MII oocyte ratio, and fertilization rate (p<0.001). Clinical pregnancy and live birth rates were higher in Group A with statistical significance compared to Group B Conclusion: Average gonadotropin dose per follicle proved to an ovarian response predictor in our study.